İNSANDA ERKEN GELİŞİM DÖNEMİ VE TERMDE GÖBEK KORDON YAPISININ IŞIK VE ELEKTRON MİKROSKOBİK DÜZEYDE ARAŞTIRILMASI - ÇETİN, AYMELEK (Fırat Üniveristesi, 1996)
The umbilical cord functions as bridge between mother and fetus during intrauterin life, playing an important role in fetus development. The structures of umbilical arteries and vein are different from the others. In this study the anatomical structure of umbilical arteries and umbilical vein were analysed. In the study the sections were obtained from umbilical cord's fetal, mid and placental regions for investigation at light microscopy level. The material consisted of 40 samples (from 11. weeks menstrual age to full- term) for light microscopy and 10 samples for electron microscopy (from 16. weeks menstrual age to full term). The specimens were cut in 5 micron thickness for light microscopy. The sections were stained as follows; Hematoxylin and eosin, PAS (periodic acid-Schiff), Crossman's triple, resorcin fuchsin (Weigert), Carmin and reticulum. The materials obtained for electron microscopy were fixed in 5 % Glutaraldehyde solution. Afterwards, the samples were fixed in osmium tetroxide solution which prepared with Millonig phosphate buffer. The tissue blocks were dehydrated in graded ethanols and embedded in Araldite. Sections from Araldite blocks were cut at 500 A° thickness. Ultrathin sections were stained with uranyl acetate saturated in 70 % ethanol and lead citrate (Reynolds) solutions. The sections were examined under electron microscope. The lumens of umbilical arteries examined light microscopically usually were stellate and narrow. The endothelial cells didn't give protrusions to the lumen. Tunica media of the arteries were thicker than the vein. The lumen of umbilical vein was smooth and wide. The endothelial cells gave protrusions to the lumen. Tunica media of the vein was thinner than arteries. The elastic fibers were numerous in the arteries, whereas they were not observed in the veins. In the early period of gestation the reticular fibers were numerous but they were scantier in full term. The collagen fibers were more numerous in the arteries than the veins.38 dönemlerde çok irileşmiş olan mitokondriyon miyadda küçülmüştü. Miyaddaki örneklerde arter endotelinde vakuolizasyon ve dejenere alanlar gözlenirken, ven endotelinde bulunmuyordu. Aa.umbilicales'in kas hücresinde bulunan mitokondriyon, granüler endoplazmik retikulum ve glikojen miktarı miyada doğru artmıştı ve sekonder lizozomlar gözleniyordu. V.umbilicalis'in kas hücresinde granüler endoplazmik retikulum miktarı miyada doğru azalmış ve glikojen artmıştı. Erken dönemlerde normal yapıda olan mitokondriyonun yapısı miyadda bozulmuştu. İntrauterin hayattaki hızlı gelişimin gerektirdiği ihtiyaçları karşılamaya yönelik görev üstlenmiş tüm dokular, optimal katkıyı sağlamak üzere değişiklik gösterirler. Göbek kordonu da bu paralelde bir takım yapısal değişiklikleri peryodik olarak gerçekleştirir.

The umbilical cord functions as bridge between mother and fetus during intrauterin life, playing an important role in fetus development. The structures of umbilical arteries and vein are different from the others. In this study the anatomical structure of umbilical arteries and umbilical vein were analysed. In the study the sections were obtained from umbilical cord's fetal, mid and placental regions for investigation at light microscopy level. The material consisted of 40 samples (from 11. weeks menstrual age to full- term) for light microscopy and 10 samples for electron microscopy (from 16. weeks menstrual age to full term). The specimens were cut in 5 micron thickness for light microscopy. The sections were stained as follows; Hematoxylin and eosin, PAS (periodic acid-Schiff), Crossman's triple, resorcin fuchsin (Weigert), Carmin and reticulum. The materials obtained for electron microscopy were fixed in 5 % Glutaraldehyde solution. Afterwards, the samples were fixed in osmium tetroxide solution which prepared with Millonig phosphate buffer. The tissue blocks were dehydrated in graded ethanols and embedded in Araldite. Sections from Araldite blocks were cut at 500 A° thickness. Ultrathin sections were stained with uranyl acetate saturated in 70 % ethanol and lead citrate (Reynolds) solutions. The sections were examined under electron microscope. The lumens of umbilical arteries examined light microscopically usually were stellate and narrow. The endothelial cells didn't give protrusions to the lumen. Tunica media of the arteries were thicker than the vein. The lumen of umbilical vein was smooth and wide. The endothelial cells gave protrusions to the lumen. Tunica media of the vein was thinner than arteries. The elastic fibers were numerous in the arteries, whereas they were not observed in the veins. In the early period of gestation the reticular fibers were numerous but they were scantier in full term. The collagen fibers were more numerous in the arteries than the veins.40 While the remnant of allantoic düet was observed (beginning from eleventh week until term) in ali periods, the remnant of vitelline düet was only observed in term. The rough endoplasmic reticulum, lipid and mitochondria in arterial endothelium were increased in term, electron microscopically. in venous endothelium rough endoplasmic reticulum which was dilated in early gestation and was narrow cişterna in full term. Mitochondria which was highly enlarged in the early period of the gestation become small in term. Although degenerated areas and vacuolization were seen in arterial endothelium but they were not seen in venous endothelium in full term samples. Amount of mitochondria, rough endoplasmic reticulum and glycogen of umbilical arteries muscle cells were increased towards full term and secondary lysosomes were observed. The rough endoplasmic reticulum of umbilical vein muscle celi decreased and glycogen increased towards full term. While it was normal in early stages the structure of mitochondria degenerated towards term. Ali the tissues which supply the needs of rapid development during intrauterin life, show changes for optimal contribution. Umbilical cord also shovvs similar structural changes periodically as parallel to these changes.
The Light microscpic and electron microscopic study of human umbilical cord`s structure from early development to full term
Keywords: Morfoloji; Morphology